The mediating role of job satisfaction at selected public universities in Afghanistan: the effect of job security on turnover intention - Mohammad Khalid, Khawrin; Sahibzada, Abdurrasheed (Journal of Management and Business Education, 2023)
The purpose of the study is to ascertain whether job satisfaction has a mediating role in the association between job security and the turnover at several public Universities in Afghanistan. The issue with the study is stated as follows. In addition to the significant impact employee, retention has on an organization's effectiveness; public colleges in Afghanistan nevertheless confront several challenges. An online Google form with a cross-sectional survey methodology was specifically utilized in this research's quantitative approach. The study’s researchers designed this normative measurement method. It has a Likert scale of five. The scale's validity and dependability were also examined. Cronbach's alphas for job security reliability, job satisfaction reliability, and job turnover reliability were 0.84, 0.68, and 0.87, respectively. An online Google form was employed to administer the convenience sampling technique. From several public universities in Afghanistan, 152 people took part. Job security had a major impact on job satisfaction. Furthermore, the intention to leave a job was significantly impacted by job security. Moreover, there was a sizable impact of job satisfaction on the intention to leave. In the association between job security and turnover intentions, job satisfaction had a strong mediating influence as well. Therefore, it is contended that job satisfaction plays a statistically positive and significant effect on job security and the intention of job turnover.